The role of sclerostin (bone proteins) and its effect on osteoporosis in postmenopausal women - Kamel Mohammed Haider; Salih Jaffat Haider (BIO Web of Conferences)
Sclerostin is a substance that inhibits the Wnt-signaling pathway, which has a detrimental effect on the bone growth process. This suggests that higher levels of selerostin may be linked to increased obesity (BMI). The primary aim of.this study was to examine the potential relationship between circulating sclerostin levels and BMI, as well as specific indices such as t-score, ESR, and biomarkers, in postmenopausal women. An investigation was performed to analyze the links between selerostin and factors such as age, gender, and composition parameters. Blood samples were collected from (90) postmenopausal women, (35) who were diagnosed with Osteoporosis, (25) samples who were diagnosed with Osteopenia, and (30) samples as a control group. Patients were diagnosed as osteoporotic and controls as usual by measuring bone mineral density (BMD) using dual-energy X-ray absorptiometry (DEXA). The results of bone turnover markers, which included SOST, showed that Osteoporotic postmenopausal have a highly significant increase (p<0.05) in means SOST (pmol/L) of 40.60±14.60, as compared with 9.52 ± 5.51 in the control group with a p-value 0.001.